การใช้โครงงานภาษาอังกฤษเรื่องการรำไทย เพื่อพัฒนาผลสัมฤทธิ์ทางการเรียนภาษาอังกฤษ ของนักศึกษาชั้นปีที่ 2 วิทยาลัยนาฏศิลปนครราชสีมา - พลอยเพิ่มพูล พิจิตรา; เดชสุภา ธวัศชา (Ratchaphruek Journal, 2015)
ผู้เรียนส่วนใหญ่มีปัญหาในการใช้ภาษาอังกฤษ ไม่มีทักษะในการสื่อสารด้วยภาษาอังกฤษเพียงพอ ทำให้ขาดความมั่นใจในการนำความรู้และทักษะในสาขาวิชาชีพเฉพาะที่เรียนเพื่อสื่อสารด้วยภาษาอังกฤษ การวิจัยนี้ต้องการที่จะศึกษาผลของการเรียนภาษาอังกฤษผ่านการสอนโดยใช้โครงงานเกี่ยวกับการรำไทยเพื่อพัฒนาผลสัมฤทธิ์ทางการเรียนภาษาอังกฤษของนักศึกษาชั้นปีที่สอง วิทยาลัยนาฏศิลปนครราชสีมา, สถาบันบัณฑิตพัฒนศิลป์ กลุ่มตัวอย่างประกอบด้วยนักศึกษา จำนวน 16 คน ที่ลงทะเบียนเรียนในรายวิชาภาษาอังกฤษเพื่อการแสดง ในปีการศึกษา 2557 ดำเนินการทดลองโดยใช้เครื่องมือในการวิจัย คือ แผนการสอนที่จัดกิจกรรมการเรียนรู้โดยใช้โครงงานภาษาอังกฤษเกี่ยวกับการรำไทยแบบทดสอบวัดผลสัมฤทธิ์ทางการเรียน และแบบสอบถามความพึงพอใจ สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน และค่าที (t-test) ผลการศึกษาพบว่า ผลการเรียนภาษาอังกฤษดีขึ้น คะแนนเปรียบเทียบผลสัมฤทธิ์ ทางการเรียนภาษาอังกฤษหลังเรียนสูงกว่าก่อนเรียน นอกจากนี้ ผู้เรียนมีความเห็นในเชิงบวกต่อการเรียนการสอนโดยใช้โครงงานภาษาอังกฤษเกี่ยวกับการรำไทยเพื่อการเรียนรู้ภาษาอังกฤษ English Project Work Instruction on Thai Dances to Enhance English Learning Achievement of Second Year Students at Nakhon Ratchasima College of Dramatic Arts Most students have difficulties with English. They are not confident to use English because they have inadequate communicative skills. They have difficulties in applying their language skills and knowledge in specific field to complete a language task. This research seeks to investigate the effects of learning English through project work instruction on Thai Dances lessons to improve students’ English achievement of second year students at Nakhon Ratchasima College of Dramatic Arts, Bunditpatanasilpa Institute, Thailand. The sample consisted of 16 second-year students enrolling in English for Acting Course in the second semester, academic year 2014. The research instruments used in the study were six lesson plans, an English achievement test and a questionnaire. The results were analyzed by using the mean, standard deviation and t-test. The result of the study indicated that the students’ English achievement had been improved. A comparison of the means of the pre- and post-tests informed that the post-test score was higher than the pre-test one. In addition, the students had very positive opinion towards using project work instruction on Thai Dances when learning English.